209k views
3 votes
PLEASE HELP

X + Y = 6
X + Y = 4

PLEASE HELP X + Y = 6 X + Y = 4-example-1

2 Answers

5 votes

Answer:

C. (5,1)

Explanation:

Well first we need to single out y in the following equation,

x - y = 4

so,

-x to both sides -y = -x + 4

divide the - by everything y = x - 4.

Now that we have our two equations.

x + y = 6

y = x - 4

We can substitute the y in the x + y = 6 for x - 4

x + x - 4 = 6

2x - 4 = 6

Add the 4

2x = 10

Divide the 2

x = 5.

Now that we have the x we can plug it in for x in x + y = 6

5 + y = 6

-5 to both sides

y = 1

So the solution is (5,1)

For more proof look at the image below.

PLEASE HELP X + Y = 6 X + Y = 4-example-1
1 vote

Answer: C) (5,1)

Explanation:

adding both equations, we get 2x = 10

which gives, x = 5

putting this value of x in first eq, we get

5 + y = 6

which gives y = 1

hence answer is (5,1)

User TestTester
by
4.3k points